(untitled) (International Journal of Nursing Education, 2020)
Background: Head traumatic is a condition where the head structure getting bump outside and having somepotential to get brain function disruption. The patients assessment with head traumatic can use traumaticscore, by using traumatic score will give quantitative assessment so it will be shown the traumatic degreeand assessing the mortality patient.Purpose: Revised traumatic score is the assessment physiologist by doing data summarized that includesystole blood pressure, respiration, and Glasgow Coma Scale for knowing the patient mortality in headtraumatic.Method: This systematic review is begin by making question, determining the objectives then finding theappropriate key words to identify searching data that is need with the method and the objectives “AND” and“OR”. After getting the data searching in 2005 up to 2019 by using database international request, pubmed,science direct and continue with PRISMA flow diagram and JBI critique tool up to get 6 articles that relevantto be analyzed be systematic review.Result and Discussion: Traumatic Scoring with revised traumatic score is a physiologist scoring systemthat is used as medical instrument hospital that can help to determine the traumatic patients whether caringin primer hospital ormain traumatic.Conclusion: Revised traumatic score is one of the traumatic assessment that able to know the patientsmortality with head traumatic by using assessment indicator that is systole blood pressure, respirasi andGlasgow Coma Scale.